WOMEN IN TOP ECHELON POSITIONS AND THEIR EFFECTS ON CARBON EMISSION DISCLOSURE: EVIDENCE FROM AN EMERGING NATION - Saheed Olanrewaju Issa; Abdulkadri Toyin Alabi; Abdulbaki Teniola Ubandawaki (Gusau Journal of Accounting and Finance)
Gender diversity in leadership roles and carbon emissions disclosure are two subjects that are generating attention in the corporate landscape. Hence, this study aims to examine the impacts of women in top-echelon positions on carbon emission disclosure of Nigerian companies during the years 2012–2021. Content analysis was employed on the annual report and sustainability report of 12 sampled listed deposit money banks in Nigeria to capture data on carbon emissions. The collected data were analyzed with the aid of the generalized least squares (GLS) multiple regression technique. Using 120 firm-year paneled observations, the result of the GLS showed that women as CEOs, board members, and audit committee members are not a significant determinants of corporate carbon disclosure. The findings have significant implications both in theory and practice, as they contribute to the ongoing discussion about women in governance and corporate sustainability.